Petrology of the micaceous Koidu and Tongo - Tonguma kimberlites, Man Craton, Sierra Leone - Viljoen, Anton (Department of Geological Sciences, 2023)
Sierra Leone contains two Jurassic-aged diamondiferous volcanic clusters, namely Koidu and Tongo-Tonguma (hereafter referred to as Tongo), consisting of eruptive pipes at Koidu and NESW trending dikes at both Koidu and Tongo. Petrographically, the diamondiferous rocks from both clusters have features of both micaceous kimberlites and unevolved Kaapvaal lamproite, making classification ambiguous. To successfully classify and constrain the petrogenesis of these rocks, a combination of detailed petrography, and phlogopite, spinel and olivine chemistry is used in this study. The Koidu rocks are predominantly macrocrystic in texture, whereas the Tongo rocks can broadly be separated into macrocrystic and aphanitic varieties. Olivine is present as macrocrysts and microcrysts, while phlogopite is occasionally present as macrocrysts and abundantly present as groundmass microcrysts (33 vol.% average). Other groundmass minerals include spinel, perovskite, apatite, and calcite set in a base of serpentine possibly containing secondary carbonate. These characteristic features can be present in both micaceous kimberlites and unevolved Kaapvaal lamproites, making classification based on petrography ambiguous. Phlogopite and spinel have similar compositional trends for both Koidu and Tongo, comparable to trends observed for archetypal kimberlites rather than lamproites. This in combination with previously studied trace element geochemistry and isotopic compositions from rocks within the Tongo cluster, indicate characteristics of an archetypal kimberlite. The overall phlogopite abundances further indicate that these rocks are micaceous kimberlites. Olivine core compositions are divided into Mg-rich (Fo >89) and Fe-rich (Fo < 89) endmembers, with Koidu and Tongo cores being dominantly Mg-rich with fewer Fe-rich cores. The overall olivine core compositions range between Fo 84.7 to 94.5 for Koidu and between 83.2 to 94.6 for Tongo. The Mg-rich olivine cores often contain intensely resorbed margins and no groundmass inclusions, consistent with a xenocrystic origin, whereas the Fe-rich population have resorbed margins to a lesser extent and are interpreted to be derived from a Cr-poor megacryst suite. Olivine rim compositions have Fo contents which are relatively homogenous, with compositional overlaps observed between Tongo and Koidu. Olivine rims often contain mineral inclusions of groundmass spinels and are interpreted as having crystallized from a magma. Previous models have suggested that olivine chemistry and groundmass mineralogy in worldwide diamondiferous rocks can be used to constrain their origin and evolution. However, the Koidu-Tongo rocks are the first example where multiple kimberlite clusters do not align with these models. The Koidu-Tongo rocks are highly micaceous and contain Mg-rich olivine core-rim compositions and correspond with Kaapvaal lamproites and so an alternative model has been suggested where the rocks are likely derived from the asthenosphere, like a typical kimberlite, but assimilated phlogopite-rich material in the SCLM.